Environmental Factors Affecting Carbon Stock in Land Use Rights (HGU) Land in Tanah Laut Regency, South Kalimantan Province - Lutfia Nursetya Fuadina; Agung Nugroho Bimasena; Nur Aliyyah Irsal (Universitas Diponegoro Publishing Group, Indonesia, 2026)
By granting Land Use Rights (HGU) for plantation and agricultural sectors, which in the future is expected to facilitate carbon trading as well, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) plays a crucial role in adapting for climate change. However, the authorities claimed that implementing the Polluter Pay Principles (PPP) for companies producing GHG emissions, such as palm oil plantations, are real steps in increasing the potential for carbon absorption and trading in Indonesia. Therefore, efforts are needed to clarify this statement by analyzing the impact of vegetation cover converted from forest to HGU areas towards the carbon stock values. The purpose of this study was to identify the variables influencing the spatial distribution of carbon stock values in the Tanah Laut Regency's HGU area. In order to map regions with high carbon stocks and meet emission reduction goals, the findings are then utilized to generate policy suggestions in the domain of sustainable plantation. The research employed quantitative methods alongside spatial analysis techniques, as well as qualitative methods through interviews with stakeholders in HGU management, including the Ministry of ATR/BPN, the South Kalimantan Regional Office, the Tanah Laut Regency Government, and HGU holders. The analysis results indicate that the carbon stock value differs across each HGU commodity, specifically rubber, cocoa, and palm oil. The mapping results of carbon stock distribution reveal that areas with minimal conversion possess high potential for carbon absorption. The Geographically Weighted Regression (GWR) analysis indicates that each variable influences locations differently. Water quality index and built-up land area show opposite values to carbon stock. The forest area has a positive value so that increasing forest area in a location will be directly proportional to the increase in carbon stock value, while the HGU area has a range of positive to negative values. It is expected that the study's findings will contribute to manage HGU permits more sustainably by taking environmental issues into account, particularly regarding assessing carbon stocks.